Age at Sexual Debut and Subsequent Sexual Partnering in Adulthood Among American Men. (July 2014) - Nield, Jennifer; Magnusson, Briana M.; Chapman, Derek A.; Lapane, Kate L.
This study examined the association of sexual debut and sexual partnering among men in the United States aged 21 to 44 years who participated in the 2006-2010 National Survey of Family Growth. Age at debut was categorized as <15 years, 15 to 17 years, and ≥18 years to permit comparison with previous research. Sexual partnering was defined as being concurrent, serial monogamist, or monogamist in prior year. Eleven percent reported concurrent partnerships and 6% serial monogamy. Sexual debut <15 and 15 to 17 years was associated with concurrency (adjusted odds ratio [aOR] < 15 = 2.22; 95% confidence interval [CI] = 1.37-3.61; aOR 15-17 = 1.69; 95% CI = 1.05-2.74). Irrespective of age at sexual debut, interventions to reduce risky lifetime number of partners may prevent risky sexual behavior in early adulthood and later in life.